Serum Stabilities and Antiviral Activities of Chemically Modified Peptides Against Dengue Serotypes 1–4 - Lee, Michelle Felicia *; Mohd Ishtiaq, Anasir; Poh, Chit Laa * (Elsevier, 2024)
Dengue presents a major public health concern in over 100 countries due to the absence of an effective vaccine and antiviral therapy against all four dengue virus (DENV) serotypes. Several antiviral peptides were previously reported to inhibit at least three or all four DENV serotypes. Chemical modifications such as d-amino acid substitutions, polyethylene glycol (PEG)ylation, and cyclization could be applied to peptides to improve their biological activities and stability in serum. The PEGylated peptide 3 (PEG-P3) was identified to be the most promising antiviral candidate as it demonstrated good inhibitory effects against all four DENV serotypes during the pre- and post-infection stages, Based on the RP-HPLC and LC/MS analysis, peptide 4 was identified to be more stable in human serum than peptide 3, with 78.9 % and 41.6 % of the peptides remaining after 72 h of incubation in human serum, respectively. Both peptides were also able to retain their antiviral activities against specific DENV serotypes after 72 h incubation in human serum. PEG-P3 was found to be more stable than the unmodified peptide 3 with 89.4 % of PEG-P3 remaining in the human serum after 72 h of incubation. PEG-P3 was able to retain its inhibitory effects against DENV-1 to 4 after 72 h of incubation in human serum. This study provided insights into the antiviral activities and stabilities of the unmodified and chemically modified peptides in human serum.